2018
DOI: 10.4103/1673-5374.232530
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with NADPH oxidase inhibitor apocynin alleviates diabetic neuropathic pain in rats

Abstract: Increased reactive oxygen species by the activation of NADPH oxidase (NOX) contributes to the development of diabetic complications. Apocynin, a NOX inhibitor, increases sciatic nerve conductance and blood flow in diabetic rats. We investigated potential protective effect of apocynin in rat diabetic neuropathy and its precise mechanism of action at molecular level. Rat models of streptozotocin-induced diabetes were treated with apocynin (30 and 100 mg/kg per day, intragastrically) for 4 weeks. Mechanical hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…9 Increased reactive oxygen species by the activation of NADPH oxidase contributes to the development of diabetic neuropathic pain. 32 In the present study, we provided the evidence to prove for the first time that G6PD in DRGs was involved in the process of diabetic neuropathic pain. We showed that the mRNA and protein expression levels of G6PD in L4-L6 DRGs were significantly lower in diabetic rats than in age-matched CON rats.…”
Section: Discussionmentioning
confidence: 57%
“…9 Increased reactive oxygen species by the activation of NADPH oxidase contributes to the development of diabetic neuropathic pain. 32 In the present study, we provided the evidence to prove for the first time that G6PD in DRGs was involved in the process of diabetic neuropathic pain. We showed that the mRNA and protein expression levels of G6PD in L4-L6 DRGs were significantly lower in diabetic rats than in age-matched CON rats.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, through ionic mechanisms shown herein, pyrethroids or other structurally similar compounds are able to adjust the functional activities of varying types of neuroendocrine or endocrine cells, or heart cells, if similar in vivo results exist [ 6 , 7 , 11 , 12 , 13 , 50 ]. To this end, the overall findings from our study highlight an important alternative aspect that has to be taken into account, inasmuch as there is the beneficial or ameliorating effect of aPO in various pathologic disorders, such as inflammatory or neurodegenerative diseases, and heart failure [ 1 , 3 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 16 , 42 ].…”
Section: Discussionmentioning
confidence: 93%
“…Of note, this compound has been widely used as a selective inhibitor of NADPH-dependent oxidase (NOX) [2][3][4][5]. Alternatively, it has been recognized to be one of the most promising drugs in a variety of pathophysiological disorders, such as inflammatory and neurodegenerative diseases, glioma, and cardiac failure [1,3,[5][6][7][8][9][10][11] aPO has been recently shown to ameliorate cardiac function (e.g., structural remodeling) in heart failure [6,7,[11][12][13]. Pituitary cells were previously demonstrated to be expressed in the activity of NOX [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and inflammation have a main role in diabetic neuropathic pain generation [ 13 , 163 - 165 ]. Inhibition of ROS generation may contribute to the reduction of diabetic neuropathy [ 166 ]. Antioxidant applications can also be useful for the attenuation of diabetes and hyperglycemia-induced neuropathy.…”
Section: Selenium and Trp Channels In Diabetes-induced Neuropathic Pamentioning
confidence: 99%